Il matrimonio nelle decretali di Alessandro III - Santospirito, Tindaro (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2019)
Pope Alexander III committed himself, in an almost frenetic manner, to the reorganization of the matrimonial institute. Starting from the tradition of the Fathers, of the different laws and of canonists, he used the new instrument of canon law to give strength to his dispositions. If until that moment there wasn’t clarity about some characteristics of marriage, and if ecclesiastical or lay courts had jurisdiction over it, Alexander, strong in his canonical competence, made it an exclusively ecclesiastical matter and that every aspect of marriage, from engagement to minimum age, from divorce to consent, from abortion to the rat, was "positivized", making it law. Starting from the analysis of the primary sources and the historiographic debate it can be understood how Alexander certainly encountered some difficulties in establishing a single judgment; in fact, the social context influenced the decisions, so much so that at times he was accommodating at other times, instead, he imposed his decision. He was one of the most productive popes in terms of the number of decrees that have reached us through the various collections of the following centuries. The legislative contribution of Alexander in matrimonial matters was of fundamental importance, to the point that until the Council of Trent his norms remained in force without modification, and afterwards they inspired the many canonists who followed one another over time, up to the Code of Canon Law of 1929. Keywords: Papacy; Medieval Marriage; Law; Canon Law; Decrees.